Gambaran Proses Asuhan Gizi Terstandar pada Pasien Penyakit Ginjal Kronik Stadium IV - rezki putri, femilya; Sulendri, Ni Ketut Sri; Wahyuningsih, Retno; Darni, Joyeti (Student Journal Nutrition (SJ Nutrition), 2023)
Background: Chronic kidney disease is a situation where there is a decrease in kidney efficiency which occurs slowly over a long period of time and has remained stable for the last 3 months. Chronic kidney disease patients who are hospitalized are not only given health care, but also given nutritional services in the form of standardized nutritional care. Nutritional care aims to help patients solve nutritional problems by overcoming various factors that cause nutritional status to change or be unbalanced.  Research Objective: To describe the process of standardized nutritional care for patients with stage IV chronic kidney disease.  Research Method: Observational descriptive method with case studies in patients with stage IV chronic kidney disease.  Research Results: The patient on behalf of Mrs. 57 year old R was admitted to hospital with a diagnosis of stage IV chronic kidney disease. From the results of the nutritional assessment, the patient had a low level of consumption of energy, protein, fat and carbohydrates. The results of anthropometric measurements of the patient have good nutritional status. Based on laboratory results, the patient had a high serum creatinine level and the patient's Hb, erythrocyte count, hematocrit, MCH, MCHC examination results were in the low category. The results of the patient's physical and clinical examination were weak and the patient's blood pressure was high. Nutritional diagnoses that can be made include inadequate oral intake, decreased protein and sodium requirements, and changes in laboratory values ​​related to nutrition. The type of diet given is a low protein and low salt diet. The results of monitoring and evaluating the patient's food intake increased to ≥80% on the second day, the patient's nutritional status was good, there were no laboratory developments because the patient did not have another laboratory examination, and the patient's physical and clinical condition was good and the patient's blood pressure was normal.  Conclusion: After intervention for 2 days, the results of monitoring and evaluating the patient's food intake increased on the second day, reaching ≥80% for energy, protein and fat. Then, for anthropometric monitoring and evaluation, the patient has good nutritional status. Then, monitoring and evaluating laboratory data could not be carried out because the patient did not undergo another laboratory examination. Furthermore, the results of monitoring and evaluating the patient's physical and clinical condition were good and the patient's blood pressure was normal.